The Effect of Solvent Concentration Against Specific and Non Specific Parameters of Standardization: Ethanolic Extract of Papaya Seed (Carica papaya Linn.) - Reza Wilorianza; Emelda Emelda; Muhammad Abdurrahman Munir; Annisa Fatmawati (Journal of Tropical Pharmacy and Chemistry, 2023)
Papaya plants (Carica papaya L.) can be used as traditional medicine. The parts of the plant commonly used as medicine are the seeds and leaves. Assurance of the quality of the extract obtained needs to be carried out by testing specific and non-specific parameters. The aim of the study was to determine the effect of the percentage of ethanol solvent concentration on specific parameters (organoleptic, phytochemical screening, and total phenolic content) and non-specific parameters (moisture content, ash content, and specific gravity) of papaya seed extract (Carica papaya L.). This type of laboratory experimental qualitative research was done to determine the effect of the percentage of ethanol solvent concentration (70% and 95%) on specific and non-specific parameters. Specific and non-specific parameter testing is based on work procedures listed in the Indonesian Herbal Pharmacopoeia. The results of testing the specific parameters on organoleptics showed no difference in the extract obtained, which was viscous and dark brown in color with a characteristic odor. Based on qualitative phytochemical screening, 70% ethanol extract contains alkaloids, flavonoids, tannins, and saponins. However, the 95% ethanol extract was only positive for alkaloids, flavonoids, and tannins. The phenolic content test of 70% ethanol and 95% ethanol extracts was 4.31 ± 0.65 mg GAE/g and 2.69 ± 0.41 mg GAE/g, respectively (Sig 0.022 < 0.05). Extract non-specific parameter test results. The ash content test for 70% and 95% ethanol extracts was 9.5% ± 0.21% w/w and 8.5% ± 0.06% w/w (Sig 0.043 < 0.05). The respective water contents were 8.7 ± 0.11% w/w and 9.7 ± 0.26% w/w (Sig 0.046 < 0.05). The specific gravity of each obtained was 0.88 ± 0.006 % g/ml and 0.75 ± 0.006% g/ml (Sig 0.043 < 0.05). The conclusion of this study is that the concentrations of 70% ethanol  and 95% ethanol in papaya seed ethanol extract have an effect on specific parameters, namely the measurement of total phenolic content. While the non-specific parameters affect the water content, total ash content, and specific gravity.